Numerical analysis of car disc brake squeal considering thermal effects - Li, Lijie (2007)
Friction-induced vibration and noise emanating from car disc brakes is a source of considerable discomfort and leads to customer dissatisfaction. The high frequency noise above 1 kHz, known as squeal, is most annoying and is very difficult to eliminate. It was recently estimated that noise, harshness and vibration (together known as the NVH problem), including disc brake squeal, generated warranty cost of about US$ 1 billion a year to the automotive industry in North America alone. Because of the high hardware cost of experiments, numerical modelling and simulation has become an important and complementary way of studying disc brake squeal and other brake noise problems. The Dynamics and Control Research Group at the Department of Engineering, University of Liverpool, is a leading research team in this area. This paper presents their recent research work of finite element analysis of brake squeal of a real car disc brake. The temperature field in the brake and the pressure distribution at the disc and pads interface due to friction are obtained. Then the friction-induced vibration of the brake taking into account the temperature and pressure distributions is analysed by the dynamic transient analysis approach. The software package used is ABAQUS6.4 Explicit. The surface profile of the pads is also considered in the finite element mode. Numerical simulations are performed at different disc velocities and brake-line pressures. It is found that both parameters affect the temperature distribution and contact pressure distribution in the thermal and contact analysis. Results of the dynamic transient analysis show that the vibration amplitude is higher when thermal effects are included. It is believed that the disc brake model with thermal effects is more realistic and accurate.